а) х - 8 = 16 - х
x+x=16+8
2x=24
x=24:2
x=12
б) -16х = 4
x=4:(-16)
x= -1/4
в) 5х - 9 = 14 + 3х
5x-3x=14+9
2x=23
x=11.5
г) 5х/ 7 (дробь) = 10
5x:7=10
5x=10*7
5x=70
x=14
д) 2·(х -3) = - 7 · (1-х)
2x-6= -7+7x
2x-7x= -7+6
-5x=-1
x=1/5
е) 1 - 3·(х - 1) = 2 - 7 (1 - х)
1-3x+3=2-7+7x
4-3x=7x-5
-3x-7x= -5-4
-10x=-9
x=9/10=0.9
Объяснение:
Хай
а) х - 8 = 16 - х
x+x=16+8
2x=24
x=24:2
x=12
б) -16х = 4
x=4:(-16)
x= -1/4
в) 5х - 9 = 14 + 3х
5x-3x=14+9
2x=23
x=11.5
г) 5х/ 7 (дробь) = 10
5x:7=10
5x=10*7
5x=70
x=14
д) 2·(х -3) = - 7 · (1-х)
2x-6= -7+7x
2x-7x= -7+6
-5x=-1
x=1/5
е) 1 - 3·(х - 1) = 2 - 7 (1 - х)
1-3x+3=2-7+7x
4-3x=7x-5
-3x-7x= -5-4
-10x=-9
x=9/10=0.9
Объяснение:
Хай